A mindfulness-based intervention adapted to dementia caregivers: A study protocol for a randomized clinical control trial - Antoniou, Rea; Toli, Despoina Georgakopoulou; Lerner, Hannah; Callahan, Patrick; Coble, Roger; Ortiz, Bailey; Sideman, Alissa Bernstein; Shdo, Suzanne M.; Levenson, Robert W.; Ferreira, Nuno; Moskowitz, Judith T; Rankin, Katherine P. (Frontiers in Psychology, 2022)
Dementia caregiving, besides encompassing various challenges in tandem to the diagnosis of the care recipient, is associated with decreased psychological well-being and mental health. Accordingly, caregivers’ wellbeing has an impact on the quality of care they provide and on the relationship quality with the person in their care. The aim of the present study is to examine the effectiveness of a mindfulness-based intervention on relational and psychological wellbeing, tailored to the needs of dementia caregivers. This clinical trial (NCT04977245) will apply a randomized controlled mixed method design. Caregivers will be randomly allocated to either the mindfulness intervention or the active control group. The intervention arm is based on experiential learning and is targeted to promote caregivers’ well-being and empowerment. Assessments will include, standardized self-report questionnaires, task performance measures, and qualitative measures. All assessments will be held at three time points (baseline; t0, 0 months, post-intervention; t1, 2 months, and after maintenance; t2, 3 months) focused on three core domains (1. relational well-being, 2. psychological well-being, and 3. dementia patient’s lifestyle/activities). The primary outcome will be relational well-being, and data will be analyzed using linear mixed modelling.